A case report focusing on diagnosis and intervention of chronic myeloid leukemia in blast crisis (acute megakaryoblastic leukemia subtype) - Liu, Long; Xiao, Yang; Cui, Na; Zhang, Liping; Wang, Lijing; Gao, Cheng; Shi, Jingfei; Yuan, Changyong; Cui, Chao (Frontiers in Oncology, 2025)
ObjectivesTo report a chronic myeloid leukemia (CML) blast crisis case, accurately diagnose its subtype, explore suitable treatment considering patient factors, and emphasize multidisciplinary diagnosis importance.MethodsDiagnosis relied on multiple approaches: bone marrow morphology, immunophenotyping, chromosomal karyotype analysis, and fusion gene detection to identify the subtype of CML blast crisis. Given the patient’s financial constraints and drug availability, the third - generation tyrosine kinase inhibitor (TKI) orelabatinib was chosen for treatment. Minimal residual disease (MRD) was rechecked two weeks after initiating therapy to assess treatment efficacy.ResultsThe patient was diagnosed with CML blast crisis of the acute megakaryoblastic leukemia subtype (M7), presenting with BCR/ABL1 fusion gene positivity, complex karyotypic abnormalities, and secondary myelofibrosis. After two weeks of orelabatinib treatment, MRD levels significantly declined, demonstrating the therapy’s effectiveness.DiscussionThis case underscores the necessity of multidisciplinary collaboration for accurate diagnosis. Treatment selection for rare subtypes like M7 requires balancing medical need with patient - specific factors. The successful reduction in MRD validates the rationality of orelabatinib use, yet more research on treatment options for rare subtypes is warranted.ConclusionMultidisciplinary methods are crucial for diagnosing CML blast crisis. Orelabatinib shows efficacy, and more research on personalized treatment is needed.